SOSIALISASI PENGGUNAAN GOOGLE CLASSROOM PADA PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 UNTUK PENGAJAR DI WILAYAH BALIKPAPAN UTARA - Rachmasari Pramita Wardhani; Rissetridharma Simanjuntak (Universitas Tridharma, 2021)
Isolation activities and social and physical distancing restrictions have an impact on learning activities which must be able to adapt to existing conditions, and be able to implement distance learning (pjj) at every school level. If this is not resolved properly, it becomes a complex dilemma without exception, both the school and parents who are still unfamiliar with the application of online distance learning which must use a new system, namely online or virtual classes. The impact of the PSBB carried out by the government caused every activity to be carried out online to break the chain of spreading the Covid19 virus. Online learning techniques can be applied effectively by using google classroom in the field of teaching and learning. based on the problems that exist in the field, the writer wrote about the Socialization of the Use of Google Classroom in Online Learning During the Covid-19 Pandemic for Teachers in North Balikpapan Area as an Implementation of a Form of Community Service which was carried out in one of the primary schools and in the Mechanical Engineering Study Program at Tridharma University in Balikpapan. In addition to the socialization, the author also collected opinions from several respondents consisting of teachers and parents as outlined in a diagrammatic diagram of several question points. The real thing is that the use of google classroom which has been implemented as a learning medium has had a useful impact on students and parents and teachers where the application of google classroom is more effective because the material can be recorded systematically. Respondents also prefer to use applications that are easy and provide a data storage platform so that socialization of community service becomes useful. Keywords— online, media, google classroom, respondents, implementation